Studies on temperature-dependent optical and electro-optical molecular characterization of terephthal-bis 4, n-decylaniline and cholesteryl oleate. (2nd July 2016) - Govindaiah, T. N.
ABSTRACT: A binary system of terephthal-bis 4, n-decylaniline (TBDA) and cholesteryl oleate (CO) exhibits a twisted grain boundary (TGB) and induced smectic phases at different concentrations and at different temperatures. Mixtures with higher concentrations of TBDA exhibit I-N * -TGB-SmC-SmA-SmB phases sequentially when the specimen is cooled from its isotropic melt. The temperature variation of optical anisotropy has been discussed. Electro-optical and X-ray studies have also been discussed.